The enunciation in the era of light technologies and Virtual Reality - Sainati, Augusto (E|C, 2020)
Analysing light technologies means referring to those audiovisual products made with the videophone or other relatively portable recording systems. However, what matters are not so much the purely material aspects of the shooting techniques, but rather their epistemological consequences, the fact that the extension of technologies has led to forms of realization that imply a "light practice" (small crews, less binding processes than those that traditionally preside over the making of films, etc.), which in turn is likely to create new and different communication models. What characterizes the audiovisual of light technologies?